Enabling Inclusive Development Concept in Marginalized Settlement Community (Case Study: Kampung Jodipan, Kota Malang) - Kurniasari, Merisa; Hayati, Arina; Setijanti, Purwanita (Institut Teknologi Sepuluh Nopember, 2020)
The era of democratization requires city leaders to change the development paradigm to be inclusive. This is stated in goal number 11 of the SDGs document,